Ekonomi 2 Sektor - Kayla Nazwa Syabila; Mahira Setianti; Nisrina Nur Fitri (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
This community service program aims to improve students' understanding of basic economic concepts, particularly two-sector economics, which covers the roles of households and companies in economic activities. The activity was carried out at SMAS PGRI 56 Ciputat using lectures and interactive discussions tailored to the characteristics of Generation Z. The material presented covered income circulation, the relationship between production and consumption, and the interconnection of economic activities in everyday life. The results of the activity showed an increase in students' understanding of the two-sector economy concept and their ability to relate economic theory to real-world practice. This program proves that economic education in schools can be an effective means of instilling a basic understanding of economics and shaping students' critical thinking in dealing with economic phenomena.